PERANCANGAN KAWASAN ISLAMIC CENTER DENGAN PENDEKATAN GREEN ARCHITECTURE - KOROMO, RAHYUL; Banteng, Beby S.D; Ajami, Frans Mitran (Journal Of Building Architecture, 2023)
Islam is a religion which Allah has sent down to the Prophet Muhammad as a mercy to all mankind. There are three main aspects to consider, namely the aspects of Aqidah (faith), Shariah (norms and laws), and Akhlak. (moral atau budaya). The need for a container that fully informs Islam and becomes a reference place for activities that breathe Islam that can unite Muslim communities in particular in Bone Bolango district, so it is necessary a place that can accommodate activities that have Islamic nuances in one place. So we need a facility that can accommodate the three, which is an Islamic Center. The province of Gorontalo until now is still in the planning phase by the government, in Bone Bolango district which is now the research site has an area of 2.12 hectares that at the time there is already a mosque used as a place of worship of the surrounding community, Islamic Center has benefits for Hajj Jemaah which in the site planned several supporting facilities for the Hajj jemaah district of Bone bolango, This research uses qualitative methods and observations to meet the needs that exist within Islamic center, for the analysis applied that is micro and macro analysis in order to obtain criteria as initial in Islamic Centre planning. The final result of this research is the application of the concept of Green Architecture in the Islamic Center area, and also the application to the supporting facilities in it, as well as the addition of Islamic center support facilities, this application is carried out according to the appropriate conditions in the Bone Bolango district, in order to create a comfortable area for users.